The Traditional Influence on Increasing Acceptance of Commercial Smartphone Applications in Specific Regions of the Arabic World. (8th December 2021) - Bahaddad, Adel A.
Abstract : The consumer sector represents one of the key players in the diffusion of M-commerce in contemporary societies. Consumers' traditionalism has a significant impact in determining the appropriate products to offer electronically, as well as in determining the functions and information that should be offered to enable them to make the right decisions at the right time. Many characteristics and requirements in general-use commercial applications cannot be acceptable for more targeted release if they are not compatible with the target population's traditional requirements, and therefore, the M-commerce applications go to complexity level in design because of the socio-technical systems. This study is conducted in three GCC countries, Saudi Arabia, the United Arab Emirates, and Qatar on 799 participant consumers. This study focuses to determine the basic requirements for smartphones' commercial applications, including the requirements affected by different traditionalism in the studied communities.